Anthropometry of Kyrgyz children: A study on the effects of age and gender - Demirhan, Bilal; Geri, Serdar; Dzhanuzakov, Kanat; Abdyrakhmanova, Dzhiparkul; Geri, Refika; Gunay, Mehmet; Bayrakdar, Akan (Sage Publications Inc, 2025)
Background: This study was motivated by the lack of anthropometric data on Kyrgyz children and the need to better understand the effects of these data on child development. Objective: The purpose of this study is to examine the anthropometric characteristics of Kyrgyz boys and girls aged 8 to 10 years in primary education. Methods: The research was conducted across 55 primary schools in the Bishkek and Ch & uuml;y regions of Kyrgyzstan. Participants included 8-year-olds (n=1215), 9-year-olds (n=1211), and 10-year-olds (n=879), both male and female. Measurements of height, body mass, diameter and circumference were taken. The data obtained were evaluated using SPSS 25 program. Comparisons according to age groups were made by ANOVA analysis. P<0.001 was accepted as significance level. Results: Statistically significant differences were identified in terms of height and body mass across all age groups for both boys and girls (p<0.05). Additionally, significant differences were found across all age groups for both boys and girls in wrist, ankle, calf, biceps extension and flexion, chest, waist, hip, neck, and shoulder circumferences, as well as arm span and arm length (p<0.001). Furthermore, statistically significant differences were observed in shoulder, chest, patella, ankle, humerus elbow, femur knee, and chest depth diameters across all age groups for both boys and girls (p<0.001). Conclusion: As a result, it can be said that there is a proportional increase in height, body mass, circumference and diameter characteristics parallel to growth in both girls and boys in parallel with age.
Keywords: Age; Anthropometry; Children; Gender; Kyrgyzstan